Analisis Kecerdasan Emosional, Teknik Dasar, Kelincahan Futsal ditinjau Dari Prestasi Siswa SMAN 18 Makassar - Kasmad, Muhammad Rachmat; Irfan, Irfan; Bismar, Ahmad Rum; Hudain, Muh. Adnan; Anjas, Anjas (UNIVERSITAS NEGERI MAKASSSAR, 2024)
This research raises the issue of Emotional Intelligence, Basic Techniques, and Agility, towards the Achievement of Students of SMAN 18 Makassar. The method used in this research is quantitative descriptive research with Canonical Correlation. The sampling technique uses a Shuttle run test instrument with a distance of 10 meters for agility, a basic technique test for playing skills and a questionnaire questionnaire for emotional intelligence. The sampling technique used Purposive sampling technique saturated with a total sample of 30 students of extracurricular SMAN 18 Makassar. The results showed that of the 30 respondents the average value of intelligence was 168.70 and for basic techniques was 46.75, agility was 13.64, and for achievement was 17.77. As for the Median value of 30 respondents, namely for the value of intelligence as much as 169.00, and basic techniques 47.50, agility 13.94, and for achievement 18.00. Based on the average and median values, it can be concluded that emotional intelligence, basic techniques, and agility on achievement influence each other.